Metabolomics profiling for identification of potential biomarkers in chickens infected with avian leukosis virus subgroup J (ALV-J). (October 2021) - Chen, Yuan; Li, Hong-wei; Cong, Feng; Lian, Yue-xiao
Abstract: There are currently no vaccines or effective drugs to prevent the disorders caused by avian leukosis virus subgroup J (ALV-J). Hence, it is critical to identify potential biomarkers in ALV-J-infected chickens to prevent ALV-J-induced disorders. We hypothesized that ALV-J infection alters metabolic profile in chickens. In the present study, a nontargeted metabolomics approach based on liquid chromatography coupled with mass spectrometry (LC-MS) was used to find differential metabolites in plasma samples from ALV-J-infected chickens and healthy controls. The parametric statistical test (Student's t -test) and fold change analysis were used for univariate analysis. Multivariate statistical analyses included principal component analysis (PCA) and partial least squares-discriminant analysis (PLS-DA). The levels of methyl bromide, pyraclonil, hexaflumuron, lythidathion, 3-phosphoglycerol-glutathione, bis-4-nitrophenyl phosphate, 4-ketocyclophosphamide, oxidized photinus luciferin, phenyl sulfate, and aryl sulfate significantly decreased, whereas the levels of 2-methylthiobenzothiazole, irinotecan, methadone, 3-o-ethyl-l -ascorbic acid, and o -acetylneuraminic acid markedly increased in ALV-J-infected chickens as compared to those in healthy controls. These data provide metabolic evidence and potential biomarkers for ALV-J-induced alterations in plasma metabolism. Highlights: Plasma metabolomic profiles showed a significant difference between the ALV-J-infected chickens and healthy controls. These data provided metabolic evidence and putative biomarkers for ALV-J infection-induced alterations in plasma metabolism.